Pengaruh Sistem Informasi Akuntansi Terhadap kinerja Pegawai Puskesmas di Lingkungan Pemerintah Kota Pekanbaru dengan Budaya Organisasi sebagai Variabel Moderasi - Ricardo, Ricardo; Trisna, Wen Via (Akuntansi & Ekonomika, 2023)
Employee performance and achievement of the goals of an organization are greatly influenced by the success of employees in carrying out their duties. The research method used is a quantitative approach, which is based on the philosophy of positivism used on certain populations or samples. This research uses two types of regression, namely multiple regression analysis and moderated regression analysis. The test results of tests carried out by the Accounting Information System it does not have a significant effect on Employee Performance. This means that the Accounting Information System variable has no significant effect on employee performance. It can be concluded that the interaction of the Accounting Information System variables and organizational culture has no significant effect on employee performance.